Influence of ethnicity in optimizing antiepileptic drug dosing : a comparison of Malay, Chinese and Indian populations in Malaysia - Manan, Mohamed Mansor (1999)
Reports of inter-ethnic differences in metabolism for phenytoin and carbamazepineh have raised questions concerning the importance of monitoring serum levels to the standardised population therapeutic concentrations. Although the pharmacokinetics of phenytoin, carbamazepine, valproic acid and phenobarbitone displayed both intra and inter-individual variations, the influence of ethnicity is still unclear. This thesis has thus set its objectives of investigating the impact of ethnicity on the efficacy of these therapeutic ranges and pharmacokinetics of these drugs. A total 1554 serum concentrations were randomly selected by a set of criteria from 470 Malays, 423 Chinese and 322 Indian of adult and paediatric patients. The Mantel-Haenzel method was used to estimate for inter-ethnic differences in response to the defined therapeutic ranges. The influence of ethnicity on pharmacokinetics was examined by the test of heterogeneity of the slopes estimates in the linear relationship of either serum concentration or clearance to dose. Coefficient of variation on the ratios of the above relationships was used to measure for inter individual variation. The results showed a highly variable response to treatment within the defined therapeutic ranges. Therapeutic response is not dependent on ethnicity and age although the latter was determined on carbamazepine and valproic acid treated patients only. The pharmacokinetics of carbamazepine, valproic acid and phenobarbitone showed high inter-individual variations and were unaffected by weight, age or ethnicity. Similar high inter-individual variation for phenytoin pharmacokinetic parameters (Km and Vmax) were observed. However, Km and Vmax(mg/day) of adult Chinese patients were significantly lower than Malay or Indian patients. The relationship between Km and Vmax and age or weight were insignificant. These findings demonstrate that Malaysian patients only differed in handling phenytoin therapy and support the use of ethnic specific phenytoin pharmacokinetic parameters during therapy.